Triclinic polymorph of bis[2-methyl-3-(pyridin-2-yl)imidazo[1,5-a]pyridin-2-ium] tetrachloridocadmium(II) - Васильєва, Ольга Юріївна; Бувайло, Олена Анатолївна; Кокозей, Володимир Миколайович; Evgeny A. Goreshnik (International Union of Crystallography (IUCr), 2024)
The crystal structure of the title organic–inorganic hybrid salt, (C13H12N3)2-[CdCl4], (I), has been reported with four molecules in the asymmetric unit in a monoclinic cell [Vassilyeva et al. (2021). RSC Advances, 11, 7713–7722]. While using two different aldehydes in the oxidative cyclization–condensation involving CH3NH2·HCl to prepare a new monovalent cation with the imidazo[1,5-a] pyridinium skeleton, a new polymorph was obtained for (I) in space group P1 and a unit cell with approximately half the volume of the monoclinic form. The structural configurations of the two crystallographically non-equivalent organic cations as well as the geometry of the moderately distorted tetrahedral CdCl42–dianion show minor changes. In the crystal, identically stacked cations and tetrachlorocadmate anions form separate columns parallel to the a axis. The loose packing of the anions leads to a minimal separation of approximately 9.53 A˚ between the metal atoms in the triclinic form versus 7.51 A˚ in the monoclinic one, indicating that the latter is packed slightly more densely. The two forms also differ by aromatic stacking motifs. Similar to the monoclinic polymorph, the triclinic one excited at 364 nm shows an intense unsymmetrical photoluminescent band with maximum at 403 nm and a full width at half maximum of 51 nm in the solid state.
Keywords: crystal structure; CdII; organic–inorganic hybrid; tetrahalometallate; photoluminescence